2020
DOI: 10.4093/dmj.2019.0042
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Probiotics and Salvia miltiorrhiza Polysaccharide Alleviates Hepatic Steatosis via Gut Microbiota Modulation and Insulin Resistance Improvement in High Fat-Induced NAFLD Mice

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) increases the risk of hepatocellular carcinoma, which is currently the leading cause of obesity-related cancer deaths in middle-aged men. Methods: Probiotics with lipid-lowering function were screened from the fecal microbiota of healthy adults. Polysaccharide from different sources was screened for improving insulin resistance. The combination of probiotics and Salvia miltiorrhiza polysaccharide (LBM) was investigated for alleviating hepatic steatosis. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 51 publications
2
58
0
1
Order By: Relevance
“…Moreover, synbiotics containing Lactobacillus paracasei N1115 and fructo-oligosaccharides alleviate NAFLD in mice, resulting in improving lipid metabolism with inhibiting the production of LPS, as well as downregulating related molecular targets like TLR4 and NF-κB [ 82 ]. Furthermore, the synbiotics containing Bifidobacterium bifidum V, Lactobacillus plantarum X, and polysaccharide from Salvia miltiorrhiza revealed a better beneficial effect on improving NAFLD and inhibiting LPS production than the single agent [ 83 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…Moreover, synbiotics containing Lactobacillus paracasei N1115 and fructo-oligosaccharides alleviate NAFLD in mice, resulting in improving lipid metabolism with inhibiting the production of LPS, as well as downregulating related molecular targets like TLR4 and NF-κB [ 82 ]. Furthermore, the synbiotics containing Bifidobacterium bifidum V, Lactobacillus plantarum X, and polysaccharide from Salvia miltiorrhiza revealed a better beneficial effect on improving NAFLD and inhibiting LPS production than the single agent [ 83 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…The estimated global prevalence of NAFLD is 25%, which is as high as 30% in some countries [1]. Recent clinical researches have revealed that diabetes plays an important role in the progression of NAFLD [2,3] and has become a strong predictor of non-alcoholic steatohepatitis (NASH) and liver fibrosis [4]. However, there is still a lack of effective treatment for NAFLD [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gardenia jasminoides Ellis is also an ingredient of two traditional Chinese formulae, Yinchenhao Decoction and Qushi Huayu Decoction, both of which have been shown to reduce hepatic fat accumulation in rats [13]. Likewise, many in vivo studies have demonstrated the hepatoprotective and hypolipidaemic effects brought about by other SZW ingredients such as Cudrania cochinchinensis [14], Poria cocos [15,16], Ilex asprella [17], Salvia miltiorrhiza [18][19][20], Cortex Lycii [21], and Amomum villosum [22]. Although the exact mechanisms of the combination of these ingredients in SZW on the alleviation of NAFLD, as well as the possible synergy involved, remain to be determined, taken together with its effect on body weight, serum total cholesterol and triglyceride, SZW was demonstrated to show an improvement of liver function in this NAFLD mouse model.…”
Section: Discussionmentioning
confidence: 99%